Two-list Thanksgiving - Whan, Christine (Beaming Books, 2025)
"What does Thanksgiving dinner look like when both sides of the family come together? When it's time to shop for ingredients, a girl makes two lists--one for the local market and one for the Korean market! Carrots for japchae and turkey stuffing. Whipped cream for the pumpkin pie. Shrimp for pajeon, short ribs for galbi, and cinnamon for the yams. And don't forget the kimchi! Thanksgiving is going to be delicious! Thanksgiving Day is full of food and family, football and conversation, and of course, giving thanks. By the end of the meal, she has a newfound love for her family's two distinct cultures. Two-List Thanksgiving celebrates the beauty of blending traditions of all family backgrounds to create a truly multicultural holiday celebration."--